Content, Structure, and Delivery Characteristics of Yoga Interventions for Managing Hypertension: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Nalbant, Gamze; Hassanein, Zeinab M.; Lewis, Sarah; Chattopadhyay, Kaushik (Frontiers in Public Health, 2022)
Objectives This systematic review aimed to synthesize the content, structure, and delivery characteristics of effective yoga interventions used for managing hypertension and to compare these characteristics with ineffective interventions. Design and Method The JBI and the PRISMA guidelines were followed in this systematic review. RCTs conducted among hypertensive adults were included. RCTs reporting at least one of the major components of yoga (i.e., asana, pranayama, and dhyana and relaxation practices) and comparing them with no intervention or any intervention were eligible. Sixteen databases were searched for published and unpublished studies without any date and language restrictions till March 15, 2021. Results The literature search yielded 13,130 records. 34 RCTs (evaluating 38 yoga interventions) met the inclusion criteria. Overall, included studies had low methodological quality mostly due to inadequate reporting. Yoga reduced SBP and DBP compared to a control intervention (MD −6.49 and −2.78; 95CI% −8.94– −4.04 and −4.11– −1.45, respectively). Eighteen, 14 and 20 interventions were effective in improving SBP, DBP, or either, respectively. 13 out of 20 effective interventions incorporated all the 3 major components of yoga and allocated similar durations to each component whereas ineffective interventions were more focused on the asana and duration of asana practice was longer. The most common duration and frequency of effective interventions were 45 min/session (in 5 interventions), 7 days/week (in 5 interventions), and 12 weeks (in 11 interventions) whereas the most common session frequency was 2 days a week (in 7 interventions) in ineffective interventions. Effective interventions were mostly center-based (in 15 interventions) and supervised (in 16 interventions) and this was similar with ineffective interventions. Conclusion Despite the low quality and heterogeneity of included studies, our findings suggest yoga interventions may effectively manage hypertension. The differences between the effective and ineffective interventions suggest that effective yoga interventions mostly incorporated asana, pranayama, and dhyana and relaxation practices and they had a balance between these three components and included regular practice. They were mostly delivered in a center and under supervision. Future studies should consider developing and evaluating an intervention for managing hypertension using the synthesized findings of the effective interventions in this review. Systematic Review Registration [PROSPERO], identifier [CRD42019139404].